Understanding the benefits of extrinsic emotion regulation in depression - Massarwe, Atheer; Cohen, Noga (Frontiers in Psychology, 2023)
Depression is a serious psychiatric illness that negatively affects people's feelings, thoughts, and actions. Providing emotion regulation support to others, also termed Extrinsic Emotion Regulation (EER), reduces depressive symptoms such as perseverative thinking and negative mood. In this conceptual review paper, we argue that EER may be especially beneficial for individuals with depression because it enhances the cognitive and affective processes known to be impaired in depression. Behavioral studies have shown that EER recruits processes related to emotion regulation, cognitive empathy, and reward-related processes, all reduced in depression. Neuroimaging data show that these beneficial effects of EER may be mediated by the recruitment of brain regions related to emotion regulation and stress reduction (e.g., ventrolateral prefrontal cortex), regions involved in empathy (e.g., medial prefrontal cortex), and reward-related brain regions (e.g., ventral striatum). This conceptual review sheds light on the mechanisms underlying the effectiveness of EER for individuals with depression and therefore offers novel avenues for treatment.